Los Incas - McKissack, Pat, 1944-2017. (Chicago : Childrens Press, 1988)
Traces the rise of the Incan civilization with emphasis on their culture, social structure, government, economy, and the fatal encounter with the Spanish conquistadors which brought about the end of their society.
Translation of: The Inca.
Includes index.
Keywords: Incas -- Juvenile literature; Incas; Indians of South America; Spanish language -- Texts; Spanish language materials